The reproductive performance of East African (Bos indicus) Zebu cattle in Ethiopia. 1. Oestrus cycle length, duration, behaviour and ovulation time - Mattoni, M.; Mukasa-Mugerwa, E.; Cecchini, G.; Sovani, S. (Elsevier, 1988)
Reproductive performance of 28 East African Zebu cows in Ethiopia were investigated over a period of 217 days. Discussions and data on the length of oestrous cycle, the onset pattern of oestrus, duration of oestrus, mounting activity and vaginal mucus discharge included.